1979
DOI: 10.1099/00221287-112-1-113
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Biochemical Studies of Mutants of Penicillium chrysogenum Impaired in Penicillin Production

Abstract: Seventy-eight mutants of Penicillium chrysogenum strain NRRL 195 1, that were impaired in penicillin production, were isolated following treatment with various mutagens. Twelve that yielded about 10% of their parental penicillin titre were studied in detail. Analyses of heterozygous diploids formed between them revealed the existence of at least five complementation groups with respect to penicillin production -V, W, X, Y and Z. Most mutants belonged to group Y. A biochemical investigation of the intracellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1981
1981
1999
1999

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Of the five P. chrysogenum Npe-complementation groups isolated by Normansell et al (1979), three were shown to be on the same arm of one linkage group (Saunders and Holt, 1987), indicating that these may be genuine mutants in the penicillin biosynthetic gene cluster.…”
Section: Discussionmentioning
confidence: 99%
“…Of the five P. chrysogenum Npe-complementation groups isolated by Normansell et al (1979), three were shown to be on the same arm of one linkage group (Saunders and Holt, 1987), indicating that these may be genuine mutants in the penicillin biosynthetic gene cluster.…”
Section: Discussionmentioning
confidence: 99%
“…5 Moreover, many fungi lack known sexual cycles (the imperfect fungi), and in these fungi only limited and partial information can be obtained from the study of parasexual processes. [6][7][8] The invention of a new electrophoresis technique, pulse field gel electrophoresis (PFGE), 9 provided an important instrument for the study of fungal chromosomes. Subsequent improvements of the original system 10,11 allowed the resolution of DNA molecules up to 11 Mb.…”
Section: Approaches To the Study Of Chromosomal Rearrangementsmentioning
confidence: 99%
“…Cosynthesis between two different non-producer mutants could occur when the mutants are cofermented under suitable conditions such that an intermediate produced by one mutant is used as a penicillin precursor by the other mutant. While earlier attempts to achieve cosynthesis of penicillin have failed (Bonner, 1947;Normansell et al, 1979), we have recently reported a procedure using osmotically fragile mycelia to demonstrate cosynthesis by certain paired combinations of mutants derived from A. nidulans (Makins et al, 1980). This technique depends for its success on the treatment of mycelia with cell wall lytic enzymes and subsequent culture in osmotically buffered media containing inhibitors of cell wall regeneration.…”
Section: Introductionmentioning
confidence: 97%
“…nidulans and P. chrysogenurn altered in penicillin production have been isolated and assigned to complementation groups and the mutations have been genetically mapped (Normansell et al, 1979;C. Blake, unpublished;Holt et al, 1976;Ditchburn et al, 1976;J.…”
Section: Introductionmentioning
confidence: 98%